Metaphors in political discourse made in the two different cultural contexts = ẩn dụ trong diễn ngôn chính trị được thực hiện ở hai bối cảnh văn hóa khác nhau. M.A. Thesis Linguistics: 82202 - Lê, Thị Phương Lan (2019)
This study explored the use of metaphors in four political speeches by two U.S. presidents: Barrack Obama and Bill Clinton made in two different cultural contexts namely Vietnamese context and American context. The metaphors found in four speeches were categorized basing on Lakoff and Johnson (1980) conceptual metaphor’s framework and then compared across the contexts to see the similarities and differences.